1997
DOI: 10.1164/ajrccm.155.1.9001332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmeterol on Pseudomonas aeruginosa infection of respiratory mucosa.

Abstract: We have studied the effect of salmeterol on both P. aeruginosa interactions with the mucosa of nasal turbinate organ cultures and on pyocyanin-induced (20 microg/ml) and elastase-induced (100 microg/ml) damage to nasal epithelial cells. Organ cultures were exposed to salmeterol either by preincubation with 4 x 10(-7) M salmeterol for 30 min or by pipetting 20 microl of 4 x 10(-7) M salmeterol onto the organ culture surface immediately prior to bacterial inoculation. Infected organ cultures (8 h) had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 0 publications
6
75
1
3
Order By: Relevance
“…A series of elegant experiments by Flak & Goldman [59] have shown that TCT and LPS trigger the production of IL-1, which in turn stimulates NO production that causes cell damage. The present authors have shown that inhibition of NO synthase reduced the amount of epithelial damage caused by P. aeruginosa infection of a respiratory tissue organ culture, suggesting that the mechanism elucidated for TCT might be common to other respiratory pathogens that damage epithelial cells [60]. It is, therefore, of interest that levels of exhaled NO are elevated during exacerbations of COPD, and were not reduced acutely by intravenous corticosteroids, but did return to normal several months later when the patient was clinically stable [61].…”
Section: Bacterial Pathogenesis In Chronic Obstructive Pulmonary Diseasementioning
confidence: 58%
“…A series of elegant experiments by Flak & Goldman [59] have shown that TCT and LPS trigger the production of IL-1, which in turn stimulates NO production that causes cell damage. The present authors have shown that inhibition of NO synthase reduced the amount of epithelial damage caused by P. aeruginosa infection of a respiratory tissue organ culture, suggesting that the mechanism elucidated for TCT might be common to other respiratory pathogens that damage epithelial cells [60]. It is, therefore, of interest that levels of exhaled NO are elevated during exacerbations of COPD, and were not reduced acutely by intravenous corticosteroids, but did return to normal several months later when the patient was clinically stable [61].…”
Section: Bacterial Pathogenesis In Chronic Obstructive Pulmonary Diseasementioning
confidence: 58%
“…Salmeterol hydroxynaphthoate (Sal), a generous gift from GlaxoSmithKline (Uxbridge, UK), was dissolved in a minimum amount of glacial acetic acid (30 l), then diluted at a concentration of 2 ϫ 10 Ϫ4 M in phosphate-buffered saline (PBS), and kept at Ϫ20°C. The stock solution was used at a final concentration of 2 ϫ 10 Ϫ7 M in DMEM/F-12 previously defined as optimal for inducing airway epithelial cytoprotection (12). Solutions were buffered to a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…in urinary tract infections caused by uropathogenic Escherichia coli [132]. The PDE4 inhibitor rolipram has also shown to be effective in preventing P. aeruginosa-induced epithelial damage [133]. Also, PDE4 inhibition seems to impair host defense to Klebsiella pneumoniae infection in the pneumonia mouse model [134].…”
Section: Impact Of Anti-inflammatory Therapies On Bacterial Respiratomentioning
confidence: 99%